SAFe Beyond Budgeting : A Reflective Practitioner Viewpoint - Honkonen, Tapio (2020)
Scaled agile framework and beyond budgeting philosophies are widely used methods of scaling the software development and transforming organizations overall towards more flexible and dynamic leadership methods, environment, and way of working. This transformation is always a big leap for organization regardless of the size of it, which usually creates transformation issues like resistance for the change. This study is primarily focusing on bringing forward the right knowledge of why the transformation is for good, what are the possible pitfalls and how the organization can start the change from a software development perspective.